2023
DOI: 10.1021/acsami.2c22774
|View full text |Cite
|
Sign up to set email alerts
|

High-Performance Colloidal Quantum Dot Photodiodes via Suppressing Interface Defects

Abstract: PbS colloidal quantum dot (CQD) infrared photodiodes have attracted wide attention due to the prospect of developing cost-effective infrared imaging technology. Presently, ZnO films are widely used as the electron transport layer (ETL) of PbS CQDs infrared photodiodes. However, ZnO-based devices still suffer from the problems of large dark current and low repeatability, which are caused by the low crystallinity and sensitive surface of ZnO films. Here, we effectively optimized the device performance of PbS CQD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 50 publications
0
11
0
Order By: Relevance
“…Additionally, a localized drug delivery system is required to inhibit multidrug resistance and mitigate more severe toxicity. 157 Nanofibers encapsulating drugs present an optimal carrier for the delivery of dual drugs, 52,131,155 without the occurrence of uncontrolled release. Furthermore, they surpass the limitations of traditional drug–polymer combinations by allowing for the placement of multiple drugs within one or two layers possessing distinct polymer, chemical and physical characteristics, thereby achieving the desired release behavior.…”
Section: Functionality Of Electrostatically Spun Nanofiber Materialsmentioning
confidence: 99%
“…Additionally, a localized drug delivery system is required to inhibit multidrug resistance and mitigate more severe toxicity. 157 Nanofibers encapsulating drugs present an optimal carrier for the delivery of dual drugs, 52,131,155 without the occurrence of uncontrolled release. Furthermore, they surpass the limitations of traditional drug–polymer combinations by allowing for the placement of multiple drugs within one or two layers possessing distinct polymer, chemical and physical characteristics, thereby achieving the desired release behavior.…”
Section: Functionality Of Electrostatically Spun Nanofiber Materialsmentioning
confidence: 99%
“…It not only provides a new approach to modifying the network substrates but also lays the foundation for further practical application of coordination polymer materials in various fields, such as photoelectric devices, 51,52 antifouling materials, 53 and electrochemical sensors. 54 ■ EXPERIMENTAL SECTION Chemicals. 2, 5-dihydroxyterephthalic acid (H 4 DOBDC), 1,3,5benzenetricarboxylic acid (H 3 BTC), 1,4-naphthalenedicarboxylic acid (1,4-H 2 NDC), 1,4-benzenedicarboxylic acid (H 2 BDC), and 2-aminoterephthalic acid (H 2 BDC-NH 2 ) were purchased from Energy Chemical.…”
Section: ■ Conclusionmentioning
confidence: 99%
“…13,15−18 Previous studies demonstrated that PbS CQD infrared PDs employing a sputtered ZnO electron transport layer (ETL) exhibited lower dark current density (J d ), higher external quantum efficiency, and faster photoresponse speed than that of the device using sol−gel ZnO layer as ETL. 19 Meanwhile, iodide-capped PbS CQDs have been verified as the best choice for the active layer. 20,21 Thanks to these rapid advances, the performance of PDs has been continuously improved.…”
Section: ■ Introductionmentioning
confidence: 99%
“…The photogenerated nonequilibrium charge carriers can be fast extracted by a rectifying junction formed by n -type metal oxide semiconductors with wide bandgaps and p- type PbS CQDs treated by 1,2-ethanedithiol (EDT). Compared with p -type layers, both i -type and n -type CQD layers have been intensively studied and improved, aiming to achieve more efficient charge separation and transport. , Previous studies demonstrated that PbS CQD infrared PDs employing a sputtered ZnO electron transport layer (ETL) exhibited lower dark current density ( J d ), higher external quantum efficiency, and faster photoresponse speed than that of the device using sol–gel ZnO layer as ETL . Meanwhile, iodide-capped PbS CQDs have been verified as the best choice for the active layer. , Thanks to these rapid advances, the performance of PDs has been continuously improved.…”
Section: Introductionmentioning
confidence: 99%